Development of congklak-based ethnomathematics media for teaching fractional numbers to grade V students - Alfinda Dwi Ninggar; Arina Restian; Murtyas Galuh Danawati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This study aims to (1) develop traditional learning media using Congklak for teaching fractions in grade 5 elementary school with an ethnomathematics approach and (2) assess its effectiveness in improving student learning outcomes. Congklak was chosen for its ability to contextualize fractions engagingly, linking local culture with mathematics. The ethnomathematics approach provides a cultural framework that enhances students' understanding of fractions through meaningful cultural experiences. The research adopts the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), covering needs analysis, media design, product development, implementation, and evaluation. Instruments include validation sheets, practicality assessments, response questionnaires, and summative tests. Results show that ethnomathematics-based Congklak media significantly improves students' understanding of fractions, achieving a 96.78% success rate. Students also responded positively to its use in mathematics learning. This study contributes to the development of culture-based learning media that enhance the quality of mathematics education while promoting the preservation of local cultural values.